التطرّف في دعوى النسخ في آية السيف - سليم, سرحد أحمد; الله, محمد حسين عبد (Sulaimani Journal for Humanities, 2021)
There are tens of Quranic verses that command patience with their opponents, forgiveness and forgiveness, and also call for all people to enter peace, to turn away from the polytheists, and to those who took over from entering Islam, and it legitimized the fight to repel aggression, and to fight those who fought Muslims, or tempted them from their religion, or exempt them from their religion. ... But the jihadist groups rose to fighting in the modern era, they asserted that these verses, and religious teachings were abrogated by the verse of the sword, and remained a recitation, which exists in a sense, but it has no meaning. I discussed this issue in a scientific discussion, and I discussed it in several aspects of the issue of abrogation, and I discussed the verses that were said: It is the verse of the sword, and I discussed some of the verses that they judged as the verse of the sword, and some of them were justified by a reason that does not accept abrogation.